Prediction of Post-operative Long-Term Outcome of the Motor Function by Multimodal Intraoperative Neuromonitoring With Transcranial Motor-Evoked Potential and Spinal Cord-Evoked Potential After Microsurgical Resection for Spinal Cord Tumors - Yamada, Shinsuke; Kawajiri, Satoshi; Arishma, Hidetaka; Isozaki, Makoto; Yamauchi, Takahiro; Akazawa, Ayumi; Kidoguchi, Masamune; Kodera, Toshiaki; Shibaike, Yoshinori; Umeda, Hideto; Tsukinowa, Yu; Hagihara, Ryota; et al. (Frontiers in Surgery, 2022)
Objective: To examine the effect of transcranial motor-evoked potential on long-term outcome of motor function after microsurgical resection for spinal cord tumors. Materials and methods: Consecutive fourteen patients with spinal tumor surgically treated at the University of Fukui Hospital between 2009 and 2020 (M:F=10:4, ages ranging from 22 to 83 years (mean+ SD=58+ 21 years)) were included in this study. There were eight intra-axial tumors and six extra-axial tumors. There were four patients with hypertension, two patients with diabetes mellitus, four patients with hyperlipidemia. Three patients were under antithrombotic medication, two were under steroid medication, four were current smokers, and four were current drinkers. Manual muscle test of upper and lower extremities of the patients were examined before surgery, at two weeks after surgery, and at the final follow up. Mean follow up period was 38±37 months. McCormick scores were examined before surgery and at the final follow up. Microsurgical resection of the tumor underwent through posterior approach under transcranial motor-evoked potential (tcMEP) monitoring. Motor-evoked potential of 46 extremities were recorded during the surgery. Gross total resection was achieved in 13 of 14 surgeries. Results: The length of peritumoral edema was significantly longer in patients with deterioration of McCormick scores than in patients with preservation of McCormick scores (p=0.0274). Ratio of MEP at the beginning of the surgery to that at the end of the surgery was the only significant negative factor predicting deterioration motor function of the extremity at the final follow-up (p=0.0374, OR 1.02E-05, 95% CI 9.13E+01-7.15E+18). ROC analysis revealed the cut-off value of the ratio of MEP to predict the deterioration at the final follow-up was 0.23 (specificity 100%, specificity 88%, positive predictive value 100%, negative predictive value 88%) to predict deterioration at the final follow up. Conclusions: Ratio of MEP was the most significant negative factor predicting deterioration of motor weakness at spinal tumor surgery. The cut-off value might be changed depending on the institutions